Effects of Slash-and-Burn-Farming and a Fire-Free Management on a Cambisol in a Traditional Maya Farming System - Ebel, Roland (CIENCIA ergo-sum; Vol. 25 Núm. 2 (2018): CIENCIA ergo-sum (julio-octubre 2018)DO - 10.30878/ces.v25n2a5, 2018)
In a single study in the Yucatan Peninsula, yield and physicochemical soil properties of a traditional slash-and-burn system, milpa, were compared to a fire-free fallow management consisting in the superficial incorporation of fallow residues. In both treatments, corn, beans, and squash were associated. While corn and bean yields were equal, squash showed higher output with slash-andburn management. Burning decreased the soil content of organic matter and plant-available N, while it increased the reserves of exchangeable K, Ca and Mg, the salinity, and the bulk density. The alternative fallow management increased the N and the organic matter reservoir in the soil. The results demonstrated that a fire-free milpa requires an additional fertilization from the first year on.